Media Transnationalism and the Politics of ‘Feminised Corruption’ - Omotoso, Sharon Adetutu; Institute of African Studies; Studies, Bayreuth Academy of Advanced African (University of Bayreuth African Studies Working Papers, 2023)
As corruption threatens state sovereignty and undermines the achievement of gender parity in politics, media have been pivotal in feminising corruption among female political office holders. By feminised corruption, I refer to recent trends of typifying women as corrupt and making more women visible among the corrupt across political spaces. While scholars have engaged with feminised poverty, focus on feminised corruption in transnational context is limited. Consequently, that media transnationalism essentialises women as higher moral agents is comprehensible; what is worrisome is how media transnationalism turns back to weaponise corruption against women in public office. Could an avowal that women are the world’s proletariat be connected with feminised corruption? If transnationalism resembles the "trans" in transvestism as Judith Butler suggests, how does media feminise corruption in transnational contexts? By focusing on feminised corruption among female political office holders, this study deploys Nigeria’s Diezani Allison Madueke’s corruption saga (1) to spotlight new, comparative insight that media transnationalism shed on feminised corruption (2) to understand how moral conduct of female political office holders affect women’s political participation, and; (3) to seek feminist moral approach that could address the challenges of feminised corruption. While this study is in no way justifying corruption or seeking to exonerate anyone, it calls attention to misogynistic use of media to deprive women and discourage new entrants from venturing politics. It emphasises moral tools necessary for any meaningful involvement of women in political activities and suggests how women may use these tools to survive and thrive within political spaces across states.
Keywords: African Feminist Ethics; feminised corruption; media transnationalism; medialities